2018
DOI: 10.1093/brain/awy217
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonian signs in patients with cervical dystonia treated with pallidal deep brain stimulation

Abstract: Pallidal deep brain stimulation is an established treatment in patients with dystonia. However, evidence from case series or uncontrolled studies suggests that it may lead in some patients to specific parkinsonian symptoms such as freezing of gait, micrographia, and bradykinesia. We investigated parkinsonian signs using the Movement Disorder Society Unified Parkinson's Disease Rating Scale motor score by means of observer-blinded video ratings in a group of 29 patients treated with pallidal stimulation and a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 47 publications
(51 reference statements)
2
24
0
Order By: Relevance
“…The pallidothalamic fibers, which are the primary efferent fibers of the GPi, likely play an important role in dyskinesia suppression after DBS 22‐24 . Because ventral GPi stimulation can worsen parkinsonism, 4,5,33‐35 it is important to examine whether parkinsonism becomes exacerbated after the change in stimulation settings. Angeli and colleagues reported that, compared with GPi or GPe DBS alone, combined GPi/GPe DBS was superior to improve both parkinsonism and dyskinesia in an acute setting in 13 PD patients 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The pallidothalamic fibers, which are the primary efferent fibers of the GPi, likely play an important role in dyskinesia suppression after DBS 22‐24 . Because ventral GPi stimulation can worsen parkinsonism, 4,5,33‐35 it is important to examine whether parkinsonism becomes exacerbated after the change in stimulation settings. Angeli and colleagues reported that, compared with GPi or GPe DBS alone, combined GPi/GPe DBS was superior to improve both parkinsonism and dyskinesia in an acute setting in 13 PD patients 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, previous studies have reported for GPi-DBS in dystonia to in fact induce bradykinetic symptoms. 27,28 In direct comparison with the two cohorts shown here, we noted that bradykinetic symptoms became worse in a larger fraction of patients from the GPi-DBS cohort. When contrasting DBS connectivity profiles in the six patients in which bradykinetic symptoms worsened most with the ones in which it improved most, connectivity to cerebellar, occipital and parieto-occipital regions was associated with symptom worsening.…”
Section: Discussionmentioning
confidence: 59%
“…The induction of bradykinetic symptoms by GPi-DBS has been reported even in cohorts without Parkinson’s disease (such as dystonia), before. 27,28 Hence, as an opportunity to study this relationship further, we contrasted functional connectivity profiles calculated from the six GPi patients in which bradykinesia improved most strongly (by 67.9 ±11.6 percent) with the six ones in which bradykinesia worsened most strongly (by −58.4 ±19.7 percent). This revealed significant differences in connectivity profiles.…”
Section: Resultsmentioning
confidence: 99%
“…DBS is not a cure for dystonia and symptoms return after switching DBS off but benefits persist longer in those with more robust plasticity. While GPi DBS has proved a successful and beneficial intervention for dystonia, it has some potential side effects including stimulation-induced Parkinsonian features (Tisch et al 2007c ; Mahlknecht et al 2018 ; Kosutzka et al 2020 ). Further refinements of DBS including adaptive stimulation may allow improvement in DBS efficacy and side effect profile.…”
Section: Discussionmentioning
confidence: 99%